Analisis dan Evaluasi Sistem Absensi Digital di PT. Abdai Indonesia Menggunakan Metode Web Usability Testing - Lorinda Nabuasa; Rizal Rizal (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital transformation has led companies to adopt digital attendance systems to improve administrative efficiency. PT. Abdai Indonesia has implemented a web-based attendance system, but several issues have emerged, including a non-intuitive interface, confusing navigation, and features that do not meet user needs. This study aims to analyze and evaluate the system’s usability using the Web Usability testing method. A descriptive quantitative approach was used, with data collected through the System Usability Scale (SUS) questionnaire, direct observation, and structured interviews. The sample consisted of 21 active users from various divisions. The findings show an average usability score of 2.23 out of 5, indicating a low level of system usability. Most respondents expressed dissatisfaction and difficulty using the system, particularly in terms of interface design, navigation, and operational efficiency. Evaluation based on Jakob Nielsen’s five usability components—Learnability, Efficiency, Memorability, Error Handling, and Satisfaction—revealed that none achieved a satisfactory score. These results suggest that the system requires significant improvements, especially in user interface design and overall user experience. This research is expected to serve as a reference for enhancing the digital attendance system in the future, making it easier to use and better aligned with user expectations.